2012
DOI: 10.1021/am300459m
|View full text |Cite
|
Sign up to set email alerts
|

3D Graphene Foam as a Monolithic and Macroporous Carbon Electrode for Electrochemical Sensing

Abstract: Graphene, a single-atom-thick monolayer of sp(2) carbon atoms perfectly arranged in a honeycomb lattice, is an emerging sensing material because of its extraordinary properties, such as exceptionally high specific surface area, electrical conductivity, and electrochemical potential window. In this study, we demonstrate that three-dimensional (3D), macroporous, highly conductive, and monolithic graphene foam synthesized by chemical vapor deposition represents a novel architecture for electrochemical electrodes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
202
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(208 citation statements)
references
References 34 publications
3
202
1
2
Order By: Relevance
“…Using Equation (3), a specific capacitance of 813 Fg -1 was obtained at a low current of 3 mA from the discharge curve for NF-G/NiO, which is closer to the specific capacitance that was obtained from the CV at a scan rate of 2 mVs -1 . These values are higher than those previously reported for G/NiO composites [34], but similar to those that Dong et al [30] reported at a scan rate of 5 mVs -1 for graphene foam/NiO composite where the nickel template was etched away. This can be attributed to the high conductivity of 3D graphene sheets and the successful loading of NF-G/NiO by the SILAR method, resulting in improved electrochemical performance of the composite.…”
Section: Methodssupporting
confidence: 87%
“…Using Equation (3), a specific capacitance of 813 Fg -1 was obtained at a low current of 3 mA from the discharge curve for NF-G/NiO, which is closer to the specific capacitance that was obtained from the CV at a scan rate of 2 mVs -1 . These values are higher than those previously reported for G/NiO composites [34], but similar to those that Dong et al [30] reported at a scan rate of 5 mVs -1 for graphene foam/NiO composite where the nickel template was etched away. This can be attributed to the high conductivity of 3D graphene sheets and the successful loading of NF-G/NiO by the SILAR method, resulting in improved electrochemical performance of the composite.…”
Section: Methodssupporting
confidence: 87%
“…[ 98 ] Among these conductive materials, graphene is an emerging conductive material because of its extraordinary properties such as electrical conductivity, exceptionally high specifi c surface area, and electrochemical potential window. [ 99 ] It has been demonstrated that graphene-based substrates are not only biocompatible but also can improve neural cell growth. When investigate the effects of graphene on the electrical activity of neuronal networks, the study of graphene for tissue regeneration has provided further outstanding surprises.…”
Section: Improving Neural Electrical Performance After Electrical Stimentioning
confidence: 99%
“…Determination of dopamine, ascorbic acid and uric acid concentration is crucial, because the concentration level of these molecules in human body is closely linked to the health status. Graphene film-based electrodes as electrochemical sensors have shown high performance towards the analysis of dopamine, ascorbic acid and uric acid [104][105][106][107][108][109][110]. For example, Xia and co-workers developed a multifunctional electrochemical sensor based on N-doped graphene (NG), which can be used to simultaneously determine AA, DA and UA [105].…”
Section: Electrochemical Sensors Technologymentioning
confidence: 99%